The Role of PAI Lecturers in Improving AIK Understanding in PAI Um Students. Buton - Putra, Alvin Gonama; Rahim, Abdul; Darmayanti, Darmayanti (Journal of English Language and Education, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) lecturers in improving students' understanding of Al-Islam and Muhammadiyahan (AIK) at Muhammadiyah University of Buton. The background of this study is based on the importance of integrating Islamic and Muhammadiyah values in shaping students' character as prospective educators with noble morals and have a comprehensive religious understanding. The research approach used is qualitative with descriptive methods. Data were obtained through interviews, observation, and documentation techniques with lecturers and students of the PAI study program. The results show that PAI lecturers play an important role as facilitators, motivators, and role models in the AIK learning process. Through the application of contextual learning strategies, integrative approaches, and exemplary behavior, lecturers are able to foster understanding and practice of AIK values in students. In addition, extracurricular activities with an AIK nuance and the habit of worship also strengthen students' understanding of Islamic teachings and Muhammadiyah values. Thus, the active involvement of Islamic Education lecturers is a major factor in realizing the goals of comprehensive Islamic education at Muhammadiyah University of Buton.